Cell entry of Lassa virus induces tyrosine phosphorylation of dystroglycan. (20th December 2012) - Moraz, Marie‐Laurence; Pythoud, Christelle; Turk, Rolf; Rothenberger, Sylvia; Pasquato, Antonella; Campbell, Kevin P.; Kunz, Stefan
Summary The extracellular matrix (ECM) receptor dystroglycan (DG) serves as a cellular receptor for the highly pathogenic arenavirus Lassa virus (LASV) that causes a haemorrhagic fever with high mortality in human. In the host cell, DG provides a molecular link between the ECM and the actin cytoskeleton via the adapter proteins utrophin or dystrophin. Here we investigated post‐translational modifications of DG in the context of LASV cell entry. Using the tyrosine kinase inhibitor genistein, we found that tyrosine kinases are required for efficient internalization of virus particles, but not virus–receptor binding. Engagement of cellular DG by LASV envelope glycoprotein (LASV GP) in human epithelial cells induced tyrosine phosphorylation of the cytoplasmic domain of DG. LASV GP binding to DG further resulted in dissociation of the adapter protein utrophin from virus‐bound DG. This virus‐induced dissociation of utrophin was affected by genistein treatment, suggesting a role of receptor tyrosine phosphorylation in the process.